2018
DOI: 10.1017/s0954579418001141
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking the link between socioeconomic status and behavior problems: A second-order meta-analysis

Abstract: Substantial evidence links socioeconomic status to internalizing and externalizing behavior problems. However, it is unclear how these two categories of behavior problems relate to specific components of socioeconomic status (e.g., income, educational attainment, and occupational prestige) or overall social status. In this study, we conducted a second-order meta-analysis to estimate the average associations of income, education, occupation, and overall socioeconomic status with internalizing and externalizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 132 publications
(211 reference statements)
4
44
1
Order By: Relevance
“…They emphasize how reliable and valid measures of cultural orientation, indexed by individuals' social identities, are essential for improving our understanding of the role of cultural orientation in development. Korous, Causadias, Bradley, and Luthar (2018) conducted a second-order meta-analysis to investigate the magnitude of the association between behavior problems and specific measures of socioeconomic status (i.e., income, educational attainment, and occupational prestige) and overall social status. They identified 12 meta-analyses including 474 primary studies and 327,617 participants and found small negative associations between both internalizing and externalizing and income and education, while only externalizing was related to overall socioeconomic status.…”
Section: Assessing and Intervening In Cultural Developmentmentioning
confidence: 99%
“…They emphasize how reliable and valid measures of cultural orientation, indexed by individuals' social identities, are essential for improving our understanding of the role of cultural orientation in development. Korous, Causadias, Bradley, and Luthar (2018) conducted a second-order meta-analysis to investigate the magnitude of the association between behavior problems and specific measures of socioeconomic status (i.e., income, educational attainment, and occupational prestige) and overall social status. They identified 12 meta-analyses including 474 primary studies and 327,617 participants and found small negative associations between both internalizing and externalizing and income and education, while only externalizing was related to overall socioeconomic status.…”
Section: Assessing and Intervening In Cultural Developmentmentioning
confidence: 99%
“…In addition, socioeconomic status (SES) is widely considered to associate with individuals’ behavior and health [ 21 24 ]. Wang et al [ 25 ] mentioned that health-related behaviors could mediate the relationship between SES and elderly health.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, socioeconomic status (SES) is widely considered to associate with individuals' behavior and health [21][22][23][24]. Wang et al [25] mentioned that healthrelated behaviors could mediate the relationship between SES and elderly health.…”
Section: Introductionmentioning
confidence: 99%